Accelerating waters: an Anthropocene history of Colorado's 1976 Big Thompson Flood - Wright, Will, author; Fiege, Mark, advisor; Orsi, Jared, committee member; Howkins, Adrian, committee member; Baron, Jill, committee member (Colorado State University. Libraries, 2016)
Scale matters. But in the Anthropocene, it is not clear how environmental scholars navigate between analytical levels from local and regional phenomena on the one hand, to global Earth-system processes on the other. The Anthropocene, in particular, challenges the ways in which history has traditionally been conceived and narrated, as this new geological epoch suggests that humans now rival the great forces of nature. The Big Thompson River Flood of 1976 provides an opportunity to explore these issues. Over the Anthropocene's "Great Acceleration" spike, human activities and environmental change intensified both in Colorado's Big Thompson Canyon and across much of the world. The same forces that amplified human vulnerability to the catastrophic deluge on a micro-level through highway construction, automobile vacationing, and suburban development were also at work with the planetary upsurge in roads, cars, tourism, atmospheric carbon dioxide, and flooding on the macro-level. As a theoretical tool, the Anthropocene offers a more ecological means to think and write about relationships among time and space.